SUS: supply, access to and use of health services over the last 30 years - Viacava, Francisco; Oliveira, Ricardo Antunes Dantas de; Carvalho, Carolina de Campos; Laguardia, Josué; Bellido, Jaime Gregório (Ciência & saude coletiva, 2018)
Significant changes have been witnessed in the Brazilian health system over the last 30 years. This article outlines trends in outpatient and hospital care, staffing, and health service use during this period. There was a significant expansion of the public health network, particularly of primary care services, leading to improved access to consultations and a reduction in hospital admissions. However, there is a persistent shortage of health professionals in Brazil's public health system, particularly dentists. Despite improvements in coverage, the public system continues to face serious challenges, particularly with respect to funding, service provision, and its relationship with the private sector.